Ans) 70
Tell me if you need steps
(Am 100% sure with this answer)
Answer:
38
Step-by-step explanation:
Given that,
x = -4
f(x)=x² - 4x +6
so,
f(-4)= (-4)² - 4 . (-4) +6
=16 +16 +6
= 38
14x - 129 (I think I’m so sorry if it’s wrong)
If you meant 2x + 2x + 1 = 17: x = 4
Solve for x by simplifying both sides of the equation, then isolating the variable.<span>
</span>
If you meant <span>x2 + 2x + 1 = 17:</span> <span>x ≈ 3.1231056,−5.1231056x</span>
Solve the equation for x by finding a, b, and c of the quadratic then applying the quadratic formula. <span><span>x = −1 ± <span>√17</span></span>x</span>
Move the deciaml 2 places to left
35000.
move to the left 2 spots
350.00 so 350%